Shared genetic loci connect cardiovascular disease with blood pressure and lipid traits in East Asian populations - Peng Zhong; Chumeng Zhang; Qinfeng Wu; Xiao Chang; Xiao Chang (Frontiers in Genetics)
IntroductionCardiovascular diseases (CVDs), including myocardial infarction (MI), heart failure (HF), atrial fibrillation (AF), and arrhythmia, are major contributors to global mortality and often share overlapping risk factors and pathophysiological mechanisms. While genome-wide association studies (GWAS) have identified many loci for individual CVDs, the shared genetic architecture across related traits—particularly in East Asian populations—remains underexplored.Materials and methodsWe integrated large-scale GWAS summary statistics from East Asian populations to perform genome-wide and local genetic correlation analyses across four CVD phenotypes and five cardiometabolic traits (blood pressure and lipid levels). Using stratified LD score regression, we assessed tissue-specific heritability enrichment. Multi-trait analysis of GWAS (MTAG) was then employed to identify pleiotropic loci associated with multiple traits, with functional annotation and expression quantitative trait loci (eQTL) data used to explore biological relevance.ResultsWe observed extensive genetic correlations among CVDs and between CVDs and cardiometabolic traits, with HF showing the strongest connections to both MI and arrhythmia. Notable genome-wide correlations were found between MI and SBP (rg = 0.35, P = 1.59 × 10−14) and between HF and DBP (rg = 0.54, P = 9.84 × 10−9). Stratified heritability analyses revealed significant enrichment in heart and arterial tissues, highlighting the relevance of cardiovascular-specific regulatory elements. MTAG identified several pleiotropic loci, including established genes such as APOB and MC4R, and novel East Asian-enriched signals such as QSOX2 and GUCY1A1/GUCY1B1. Functional data indicated that QSOX2 variants regulate gene expression in arterial and cardiac tissues, implicating redox regulation in HF and hypertension pathogenesis.ConclusionOur findings provide comprehensive insight into the shared genetic determinants of cardiovascular and metabolic diseases in East Asian populations. The identification of pleiotropic and ancestry-specific loci, along with tissue-specific regulatory patterns, underscores the need for integrative multi-trait and population-informed approaches in cardiovascular genetics and risk prediction.